Development of a discrete event simulation tool for assembly line simulation - Mohd Fadzil Faisae, Ab Rashid; Nik Mohd Zuki, Nik Mohamed; Abdullah, Nasser (AIP Publishing LLC., 2023)
Discrete event simulation (DES) is a powerful tool for better decision-making. Its application can be found in almost every sector ranging from industrial to services. However, the cost of commercial DES tools sometimes makes them unaffordable for small and medium enterprises. On the other hand, the open-source DES requires good programming knowledge for model customization. This paper presents the development of the DES tool specifically for production and assembly line simulation. The developed tool known as Discrete Event Simulation for Assembly Line (DESIMAL) is flexible enough to support different types of the assembly line. Testing and validation have been conducted using an industrial case study. The result indicated that the developed DESIMAL has similar output with a small error margin (1.08% – 3.60%) compared with commercial DES software. In comparison with real problem output, DESIMAL obtained the result with an error of less than 5%. Therefore, the developed DESIMAL has been validated as an acceptable tool for assembly line simulation. The main contribution of this work is an establishment of DES tool for assembly line simulation.